A suggested Guide for Elementary School Teacher to Integrate E-Learning in Teaching Art Education - Al-EWYWID, HAEA NASSER; Al-Dosari, Mohammed Mofleh (Journal of Educational and Psychological Sciences, 2019)
The objective of the study is to design a proposed guide for the primary stage teacher and to determine its validity from the point of view of the experts and specialists. The researcher followed the descriptive approach to answer the research questions: What is the proposed scenario for building a guide for the elementary teacher; ? What is the validity of the proposed guide for the teaching of art education for the sixth grade? The answer to the first question in the design of the researcher was a proposed guide for the primary stage teacher to integrate e-learning in the teaching of art education for the sixth grade. The answer to the second question was by presenting the proposed guide to experts and specialists. The majority of the judges' (34) arbitrators out of (40) arbitrators, which means that the evidence proposed by the researcher is valid for the teaching of art education for the sixth grade primary The research has reached a number of recommendations, the most important, H. To integrate e-learning into the teaching and learning of art education for the sixth grade of elementary school by primary school teachers and to expand the conversion of courses in art education to courses incorporating technology in teaching and learning.
Keywords: primary school; teacher; integration; e-learning; teaching; art education